Online pedagogical effectiveness in online contexts: New Frontiers for Teaching Practices. - Dixon, Kathryn; Dixon, R. (2010)
A longitudinal study of students in the Training and Development program at Curtin University of Technology has been undertaken in an attempt to develop a framework which describes the dimensions of pedagogical effectiveness in online teaching and learning. The research began in 2004, and data have been collected from the sample group of students in the program from 2004-2007. As a result of analysis and review of the findings, the Online Pedagogical Effectiveness Framework (OPEF) emerged incrementally. The new framework challenges the traditional importance placed on the centrality of teaching skills and the need for student interaction in online teaching and learning, which according to this study, diminished over time. This has ramifications for the interchangeability of the roles of teacher, learner, and instructional designer peers and colleagues.